Food, Forests, and Landscapes - Solutions for Sustainable Development - Holmgren, Peter (2013)
CIFOR-IFPRI Policy Seminar "Food, Forests, and Landscapes - Solutions for Sustainable Development" with Shenggen Fan, IFPRI, Peter Holmgren, CIFOR, and Geeta Sethi, The World Bank.